2012
DOI: 10.1177/1469787412467122
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the use of text messages in mobile learning

Abstract: Nowadays, teaching and learning have been shifted from traditional classrooms to technology-supported learning environment. By offering a convenient, efficient and financially affordable information technology learning environment, mobile learning is a topic that is of considerable interest for education audiences owing to the pervasive nature of text messaging. This study investigated tertiary students’ use of text messaging in mobile learning and related areas such as their literacy levels and years of using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Two articles reported on the same study (Geng, 2013 andGeng &Disney, 2013). As Figure 1 shows, there were between two and eight articles published each year, apart from 2007 when no relevant studies were located.…”
Section: Resultsmentioning
confidence: 97%
“…Two articles reported on the same study (Geng, 2013 andGeng &Disney, 2013). As Figure 1 shows, there were between two and eight articles published each year, apart from 2007 when no relevant studies were located.…”
Section: Resultsmentioning
confidence: 97%
“…For example, Cassidy et al (2011) focused their study of technology use and preference around library services. Other researchers narrowed their studies to specific technological resources, formats, or applications such as mobile/cellular devices (Baker et al 2012;Geng 2013); social networking sites (Subrahmanyam et al 2008); and online video use (Sherer and Shea 2011). Little research has examined the academic versus nonacademic contextual use of technology by emerging adult college students.…”
Section: Developmentally Appropriate Instruction For Emerging Adultsmentioning
confidence: 99%
“…Geng studied how the use of text messaging might positively or negatively influence the levels of literacy of tertiary students, especially in terms of their reading and writing abilities, and found that it was positively related to their reading and writing ability. Her study also showed that the students' translation of text abbreviations was significantly correlated with their reading and writing levels and that the students who rated themselves higher in reading and writing had more correct translations of the text abbreviations (Geng, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, as users of text messages, pre-service teachers discuss their studies or teaching practicum with mobile phones (Geng, 2013). As one of the fastest growing types of technologies (Geng, 2013;Plester, Wood & Bell, 2008;Reid & Reid, 2005), text messaging provides pre-service teachers with an inexpensive, fast-paced and convenient channel for communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation